Effect of TDSs on nitrate removal in ROC treatment process. Issue 3 (3rd October 2016) - Eom, Hanki; Choi, Jungsu; Kim, Sungchul; Joo, Hyunjong
Abstract : Reverse osmosis concentrate (ROC) is associated with a high concentration of total dissolved solids (TDSs) which is known to affect a biological wastewater treatment. The aim of this study is to assess the effect of TDSs on the biological denitrification in ROC for biological treatment. This study focused on evaluating the changes in TDSs and substrate adsorption rates in association with polysaccharides (PSs) on the surface of microorganisms. Experiments performed with TDSs injection mode showed that NO3 − -N (nitrate) concentration in the effluent increased from 4·7 ± 1·5 to 9·5 ± 1·9 mg/L. The specific oxygen uptake rates (SOUR) and PSs were found to decrease from 66·05 ± 10·01 and 19·29 ± 5·98 to 42·56 ± 4·19 and 9·73 ± 0·80 mg O2 /g MLVSS-h, respectively. Of the specific TDSs components, cations, more specifically calcium, were adsorbed to the surface of microorganisms, and subsequently the substrate adsorption rates were decreased by approximately three times. It is believed that the transfer of substrate typically necessary for denitrification was inhibited by the adsorption of the TDSs. Therefore, physicochemical treatment prior to biological treatment must be performed to control TDSs for the treatment of ROC. It is expected that the effective treatment of ROC will contribute to improving the efficiency of biological wastewater treatment.